Systolic function of the left ventricle in patients with pulmonary hypertension on the background of chronic obstructive pulmonary disease - I. M. Fushtey; K. L. Nikolaieva (Сучасні медичні технології)
Chronic obstructive pulmonary disease (COPD) greatly affects the quality of life, significantly limiting the physical capabilities of people suffering from it. The prevalence of COPD worldwide is about 7,6 %, and it is one of the main causes of morbidity and mortality in today’s society. An urgent medical and social problem of our time is the development of pulmonary hypertension (PH) in patients with COPD. Transthoracic echocardiography is important for PH screening. It has the highest sensitivity and specificity among non-invasive examinations, and unlike catheterization of the right heart, it does not require special equipment and centers for dynamic monitoring of patients with PH. When pulmonary hypertension, there is a pronounced remodeling of the heart. At the first stage, it occurs in the right parts of the heart, and in the future, as a consequence, it is accompanied by a violation of systolic inter-ventricular interactions.